Our experience of biliary ascariasis in children - Wani M; Chechak Bashir; Reshi Farooq; Pandita Sanjay; Rather Muddasar; Sheikh Tariq; Ganie Ishfaq (Wolters Kluwer Medknow Publications, 2006)
Ascariasis is highly endemic in Kashmir valley as temperate climate and wet soil provide excellent conditions for its development. We studied 198 cases (11%) of biliary ascariasis out of 1,800 patients of worm infestation from December 2001 to December 2004 in the age group of 4-15 years. In our study, we found biliary ascariasis to be more common in female children, and most common clinical presentation was biliary colic in 143 patients, cholangitis in 28, cholecystitis in 15, liver abscess 7, pancreatitis 4 and postoperative worm infestation in 1 patient. Ultrasonography of abdomen was the diagnostic tool of choice with hundred percent results. Most of the patients were managed conservatively. ERCP was not done in children because of need of general anesthesia and difficulty in performing the procedure. Surgical intervention was required in 23 patients (cholecystectomy with CBD exploration in 5, choledochotomy alone in 13, drainage of liver abscess in 3, choledochoduodenostomy in 1 and peritoneal lavage in 1).